Enhancing Fundamental Capabilities for College English Teachers in the Context of the New Liberal Arts - Gao, Sutong (Journal of Educational Research and Policies, 2025)
The construction of new liberal arts has put forward new and higher requirements for English courses and English teachers in universities, making them face new problems and challenges. In order to actively address these issues and challenges, English teachers in universities must first focus on the goals of the new liberal arts construction and the new positioning and development direction of English courses in universities, and then enhance their core competencies and professional qualities. Starting from the actual situation of English teachers in universities, this article discusses how to enhance the professional quality and core competencies of English teachers through four aspects: professional knowledge, teaching ability, information technology ability, and research ability under the background of the new liberal arts. This provides certain assistance for the personal growth and professional development of teachers, and lays a solid foundation for the development of the English discipline and the cultivation of composite excellent talents.